2013
DOI: 10.1136/gutjnl-2013-304739
|View full text |Cite
|
Sign up to set email alerts
|

Colonic mucosa-associated diffusely adherentafaC+ Escherichia coliexpressinglpfAandpksare increased in inflammatory bowel disease and colon cancer

Abstract: ObjectiveColonic mucosa-associated Escherichia coli are increased in Crohn's disease (CD) and colorectal cancer (CRC). They variously haemagglutinate, invade epithelial cell lines, replicate within macrophages, translocate across M (microfold) cells and damage DNA. We investigated genes responsible for these effects and their co-association in colonic mucosal isolates.DesignA fosmid library yielding 968 clones was prepared in E coli EPI300-T1 using DNA from a haemagglutinating CRC isolate, and resulting haemag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
160
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(173 citation statements)
references
References 58 publications
4
160
1
2
Order By: Relevance
“…As Friswell et al [44] highlight in their review of the role of bacteria in the pathogenesis of IBD, blockade of bacterial entry via M cells represents an important target for therapies. In a very recent paper [45] , certain isolates of E. coli have been shown to be related both with colorectal cancer and IBD. The authors suggest that interventions that either reduce colonization by diffusely adherent E. coli or block their interaction with the mucosa may have preventive or therapeutic effects in colon cancer and CD.…”
Section: Adherent-invasive E Colimentioning
confidence: 99%
“…As Friswell et al [44] highlight in their review of the role of bacteria in the pathogenesis of IBD, blockade of bacterial entry via M cells represents an important target for therapies. In a very recent paper [45] , certain isolates of E. coli have been shown to be related both with colorectal cancer and IBD. The authors suggest that interventions that either reduce colonization by diffusely adherent E. coli or block their interaction with the mucosa may have preventive or therapeutic effects in colon cancer and CD.…”
Section: Adherent-invasive E Colimentioning
confidence: 99%
“…The murine macrophage lineage J774A1 cell line is a great in vitro model because of its remarkable plasticity (Franz et al, 2011;Hosokawa et al, 2011). Several recent genomic studies have used the J774A1 cell line to evaluate cytokine/chemokine activity (El Aamri et al, 2015), integrin modulation (Ferraz et al, 2016), inflammatory activity (Bohr et al, 2013), and cancer markers (Prorok-Hamon et al, 2014). These studies mainly utilized quantitative polymerase chain reaction (qPCR), a reliable and versatile technique, to evaluate gene expression under various biological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…64 Other studies have documented that mucosa-associated E.coli expressing pathogenicity islands of afimbrial adhesin (afa), long polar fimbriae (lpf) and polyketide synthase (pks) are frequently seen in IBD and colon cancer patients. 5,65 The afa and lpf operons are known to confer adhesive characteristics on E.coli for epithelial cells. 5,65 Recent studies in mouse models of colitis-associated colorectal cancer have demonstrated that pksencoding colibactin produced by mucosaassociated, adherent E.coli causes DNA damage and cell senescence, and drives tumor progression.…”
Section: Faulty Host or Bug Or Both?mentioning
confidence: 99%
“…5,65 The afa and lpf operons are known to confer adhesive characteristics on E.coli for epithelial cells. 5,65 Recent studies in mouse models of colitis-associated colorectal cancer have demonstrated that pksencoding colibactin produced by mucosaassociated, adherent E.coli causes DNA damage and cell senescence, and drives tumor progression. 66,67 The newly acquired adherent and cytotoxic characteristics of enteric bacteria are likely to stimulate host immune response through pathogen-associated or damage-associated molecular patterns, triggering the onset of proinflammatory signaling.…”
Section: Faulty Host or Bug Or Both?mentioning
confidence: 99%
See 1 more Smart Citation